Neurogenetic study of central nervous system tumors: a comparative analysis with epidemiological biomarkers to support the development of a computerized database - TOLEDO SCOPARO BARIONI, CARINA; Machado Pereira, Gustavo; Boia Ferreira, Marianna; Auswaldt Steclan, Chelin (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: This study explores the importance of genetic and epidemiological biomarkers in the identification and classification of central nervous system (CNS) tumors, focusing on mutations in the IDH1, IDH2 genes, and methylation of the MGMT gene promoter, which play crucial roles in the prognosis and treatment response of gliomas. Objective: To integrate the analysis of these biomarkers with epidemiological risk factors to support the personalization of therapeutic strategies, aiming to create a personalized database in the future. Methodology: The methodology consisted of a systematic literature review following PRISMA guidelines. Searches were conducted in the PubMed and Science Direct databases, covering studies published between 2012 and 2024. After applying inclusion and exclusion criteria, 31 articles were selected for analysis. Results: Mutations in the IDH1 gene, especially the R132H mutation, and MGMT promoter methylation were found to be key determinants in the prognosis and personalized treatment of gliomas. Environmental risk factors, such as prolonged exposure to ionizing radiation and electromagnetic fields, were significantly associated with an increased risk of developing CNS tumors. Discussion: The importance of an integrative approach combining genetic and epidemiological data was highlighted. This integration can allow substantial advances in the diagnosis, prognosis, and personalized treatment of CNS tumors. Conclusion: The study reaffirms the relevance of neurogenetic biomarkers in the personalization of therapeutic strategies and highlights the need for integrative approaches to enhance clinical interventions and improve patient outcomes.